Intellectual property \'with Chinese characteristics\': the global politics of China\'s development plans - Ido, Vitor Henrique Pinto (2021)
This thesis takes the expression intellectual property (IP) with Chinese characteristics as a departure point to reflect on the interplay between IP, industrial and innovation policies in contemporary China. Inspired by legal anthropology and political economy, it aims at highlighting what is concealed and what is elicited by the expression. In around 40 years, China went from a nearly non-existent to a very stringent IP system. It is the largest applicant of patents in the world, and actively engages at the World Trade Organization (WTO) and the World Intellectual Property Organization (WIPO). Persistent counterfeiting, access to medicines, artificial intelligence, and reduced freedom to operate are main issues at stake. In this context, the thesis compares the Made in China and the Made in China 2025, which represent the shift from an economic model based on relatively cheap manufacturing with little IP protection to the pursuits of Chinas technological dominance with hightechnology and strong IP protection. It provides a historical overview and assesses the recent amendments in the period 2019-2021, which are based on foreign pressure by the US-China trade war and the interests of domestic firms in IP protection. It also conducts an analysis of some of the main contemporary aspects of the Chinese IP system, including the expansion in IP applications, the use of national security, the creation of specialized courts, policies to create a culture of IP in schools and universities, and ostensive anti-counterfeiting policies. Subsequently, the research deals with how the IP with Chinese characteristics reverberates internationally. To that aim, it conducts an analysis of Chinas stances at the World Trade Organization (WTO) and the World Intellectual Property Organization (WIPO), where the country tends to adopt intermediary positions. This section is partly based on a series of interviews and an ethnographic experience as participant observer in Geneva (2018-2021). It also develops Chinas IP stances in the Regional Comprehensive Economic Partnership (RCEP) and its Belt and Road Initiative (BRI), as examples of its increased role in regional and bilateral IP. China conducts procedural harmonization and cooperation-based activities but does not push its own Chinese legal standards. Therefore, it concludes that there is no Chinese standard in IP, but its role as norm-maker will invariably continue to grow. This may offer opportunities for Latin America. In the following chapter, the research addresses the politics of pharmaceutical patents and Covid-19 vaccines. It provides an analysis of IP and access to medicines in China, and its adoption of multiple TRIPS-Plus norms, which largely reduces the policy space of the country to ensure affordable access to medicines. The non-IP regulatory scope of tools available to the Chinese State can limit the detrimental impacts in China but may not be enough. The chapter then assesses the pharmaceutical sector in the country, noting how Chinese companies aim at becoming global big pharma, which this is in line with Chinas aspirations to achieve technological dominance. At the World Health Organization (WHO), China has committed to treating vaccines as global public goods. At the same time, it has incentivized patenting of all technologies via fasttrack policies, and heavily invested and coordinated the Covid-19 R&D research. China has been the main provider of Covid-19 vaccines in the global south but uses it to advance its geopolitical interests. The Sinovac-Butantan partnership highlights some interactions and a transnational publicprivate regulation between China and Brazil. The chapter presents the debates on the WTO TRIPS waiver proposal and the mostly cautious, background role of China despite its key position in the access to Covid-19 vaccines. It concludes with a parallel between the idea of vaccine diplomacy and IP nationalism are correlated issues. The next chapter argues that IP is part of a nation-building process and surrounded by a specter of modernity. In contemporary China, this is associated to a forward-looking and futuristic ideal that positively values the high-tech. For this reason, the figure of the IP pirate is a public enemy to be combatted since it represents the backwards and the illicit. However, categories of copy and authenticity are not pre-existing, but constructed something which Tianducheng, a Chinese copy of Paris with its own aura, elucidates. The concluding remarks argue that China offers a lesson for countries to use their policy space to conduct IP and innovation policies differently from the expectations of Western countries. However, it does not present a techno-diverse, critical alternative: instead, it reinforces existing structures. At the very end, drawing a comparison with Brazil, the thesis concludes with the need to envision alternative intellectual properties, which should not be based on exclusionary concepts of nationalisms and the private, but rather on inclusionary ideas of global and the public.